Protein ontology instance store - Sidhu, Amandeep; Dillon, Tharam S.; Chang, Elizabeth (Springer, 2007)
Biomedical Knowledge of Proteomics Domain is represented in the Protein Ontology, whose instantiations, which are undergoing evolution, need a good management and maintenance system. Protein Ontology instantiations signify data and information about proteins that is shared and has evolved to reflect development in Protein Ontology Project and Proteomics Domain itself. Protein Ontology needs to be populated with data and information from data and information sources proteomics domain. In this chapter we explore the implementation methodology for Data and Knowledge Management in Proteomics Domain by mapping various protein data and knowledge sources to the concepts defined in the protein ontology and developing a Protein Instance Store